2017
DOI: 10.1002/jsfa.8640
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of the proteins bound by specific phage‐displayed recombinant antibodies (scFv) obtained against Brazil nut and almond extracts

Abstract: The presence of important Brazil nut and almond allergens (Ber e 2 and Pru du 6) in foodstuffs can be determined by using phage-display antibodies BE95, PD1F6 and PD2C9 as affinity probes in ELISA. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Two isoforms have been identified in almond, prunin 1 and prunin 2, which comprise native prunin (de la Cruz et al, 2017). Analyses of almond protein extract has been extensively carried out and it was found that prunin is a major component of the nut, accounting for up to 65% of the protein in the soluble extract (Zhu, 2014).…”
Section: Globulin Protein Of Sesame Seeds Amandin Protein Of Almond mentioning
confidence: 99%
“…Two isoforms have been identified in almond, prunin 1 and prunin 2, which comprise native prunin (de la Cruz et al, 2017). Analyses of almond protein extract has been extensively carried out and it was found that prunin is a major component of the nut, accounting for up to 65% of the protein in the soluble extract (Zhu, 2014).…”
Section: Globulin Protein Of Sesame Seeds Amandin Protein Of Almond mentioning
confidence: 99%